Theophrastus of Eresus : sources for his life, writings, thought and influence. Commentary volume 8, Sources on rhetoric and poetics (texts 666-713) - Fortenbaugh, William W. (Philosophia Antiqua, 2005)
This volume is a commentary on the rhetorical and poetic texts collected in the second volume of Theophrastus of Eresus: Sources for His Life, Writings, Thought, and Influence . The commentary begins with a discussion of the ancient and medieval sources from which the texts are drawn. Next comes discussion of the titles of Theophrastus' works on rhetoric and poetics. After that each text is discussed individually. In sum, Theophrastus is shown to be an important, though sometimes seriously misunderstood, contributor to the development of Greek rhetorical and poetic theory. The commentary concludes with a bibliography of the modern scholary literature followed by several indices: important Greek and Latin words, titles of works (non-Theophrastean as well as Theophrastean), persons and places, and subjects discussed in earlier sections of the commentary.